Integrating Technology into the Curriculum - Kopp, Kathleen, 1967- (Huntington Beach, CA : Shell Education, 2015)
This updated, second edition resource provides teachers with classroom-tested ideas and resources to enhance instruction and help make the integration of technology into the classroom a seamless process.
Today's technology for tomorrow's classrooms -- Technology and curriculum standards for teachers and students -- Technology to support literacy instruction in English language arts -- Technology to support content-area instruction -- Online applications to extend learning and thinking -- Moving beyond computers -- Assistive technology for special-needs students -- Assessment in the digital age -- Classroom management tips and strategies -- Professional development to strengthen technology integration.
Includes bibliographical references (pages 197-223)
"EBSCO evaluates our products based on the Web Content Accessibility Guidelines (WCAG) and the related Section 508 and EN 301 549 regulations in the US and EU. Most EBSCO products are substantially conformant with WCAG 2.2 level AA." Source: https://connect.ebsco.com/s/article/EBSCO-VPATs?language=en_US. Last accessed April 22, 2025.
Print version record.
Added to collection customer.56279.3
Keywords: Educational technology; Internet in education -- United States; Computer-assisted instruction -- United States; Educational innovations -- United States; Teaching -- Aids and devices; instructional materials; EDUCATION -- Administration -- General; EDUCATION -- Organizations & Institutions